Low frequency of mutation of epidermal growth factor receptor (EGFR) and arrangement of anaplastic lymphoma kinase (ALK) in primary pulmonary lymphoepithelioma‐like carcinoma. Issue 2 (3rd December 2019) - Yin, Kai; Feng, Hui‐Bo; Li, Lin‐Lin; Chen, Yu; Xie, Zhi; Lv, Zhi‐Yi; Guo, Wei‐Bang; Lu, Dan‐Xia; Yang, Xue‐Ning; Yan, Wen‐Qing; Wu, Yi‐Long; Zhang, Xu‐Chao
Abstract: Background: Primary pulmonary lymphoepithelioma‐like carcinoma (PLELC) is a rare and unique subtype of lung cancer. However, the prevalence of driver alterations, such as epidermal growth factor receptor ( EGFR ) mutations and anaplastic lymphoma kinase ( ALK ) rearrangements, and the response of tyrosine kinase inhibitor (TKIs) in PLELC has not been thoroughly investigated. Method: We retrospectively reviewed the genetic profiles and treatment course of 330 PLELC patients at the Guangdong Lung Cancer Institute (GLCI) from 1st January, 2008 to 30th December, 2018. We searched and analyzed related literature published in PubMed and Web of Science from 1st January, 2000 and 31th August, 2019 based on their mention of "driver mutations" and "the response of TKIs to mutant PLELC". Results: Genetic alterations of EGFR/ALK were tested in 203 patients (203/330, 61.5%). Five patients (5/175, 2.9%) had EGFR mutation and three patients (3/140, 2.1%) had ALK alteration. From the total of 15 articles identified from electronic searches, 1071 PLELC cases mentioned the driver mutations. EGFR mutation and ALK rearrangement were detected in 15 patients and one patient, respectively. In total, there were four EGFR / ALK mutant PLELC patients who received targeted therapy as palliative treatment at the GLCI and in the literature. However, there was disease progression in all cases one month after use of TKIs. Conclusion: The mutation rates of EGFR and ALK were low in PLELC. EGFR and ALK TKIs showed limited response in EGFR/ALK mutant PLELC. Further studies are needed to explore other molecular targets to optimize the therapeutic strategy for PLELC.